Sutradhara figure in the mandapa of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is a sculpture of a Sutradhara from the pilaster in the mandapa of the Mandaleshwar Mahadev Temple. He is shown standing with a yardstick in his left hand. Sutradharas were architects who designed and instructed the making of a temple. Sculptures of Sutradhara are rare.